Valorization of bamboo leaf ash in biocomposites for fibercement and 3D printing - Moraes, Maria Júlia Bassan de (2024)
The study aimed to bridge technological advancement with sustainability by evaluating the feasibility of using bamboo leaf ash (BLA) as a partial substitute for Portland cement and a source of silica for the production of the alkali activator in alkali-activated materials (AAM). Moreover, seeking to integrate the utilization of agricultural waste into the construction sector, the research investigates the viability of incorporating BLA into practical applications such as fiber cement intended for industrial purposes and 3D printing. The incorporation of PP fibers and BLA resulted in increased water demand, leading to elevated porosity and interconnected pores with rising water content. However, for formulations without accelerated aging, the mix design with 10% replacement showed improved mechanical behavior in terms of modulus of rupture (MOR - 10.2%) and limit of proportionality (LOP - 4.5%) compared to a formulation without BLA. For composites subjected to accelerated aging, the CPP1-BLA10 formulation demonstrated superior mechanical properties. It showed enhancements in LOP, Modulus of Elasticity (MOE), MOR, and Specific Energy (SE) compared to CPP1 by 8.6%, 24.5%, 16.0%, and 33%, respectively. The optimal oven time for activator production using BLA was 16 hours at 40 °C. Isothermal calorimetry tests showed changes in curves with increasing BLA content, including an extension of the dormant period and a shift in the second peak. Despite BLA causing a deceleration of reactions, AAM with BLA achieved higher final cumulative heat values than NH (206 J/g). NH-BLA0.7, NH-BLA1.0, and NH-BLA1.3 formulations obtained values of 224 J/g, 244 J/g, and 235 J/g, respectively. The curing treatment significantly influenced flexural strength, with the W treatment (immersed in water) yielding the highest strength of 6.58 MPa. Increasing the SiO2/Na2O ratio led to a significant mechanical improvement in compressive strength. There was an increase of 72.15% (NH-BLA1.3) in comparison with the formulation without BLA. The NH-BLA1.3 formulation maintained flowability for 100 minutes compared to 5 minutes for NH. While NH-BLA1.0 showed suitable extrudability, adjustments are needed for better buildability. Mechanical testing revealed minor differences across loading directions. Therefore, the 3D-printed AAM demonstrated low anisotropy and satisfactory strength values when BLA was used as a silica source for activators, suggesting its potential as an alternative to commercial activators despite its simple production process. The utilization of sustainable materials, particularly those derived from agro-industry, is crucial for civil development. Despite facing challenges, these materials hold significant promise due to their local availability and large-scale production. This study explored the potential applications of agro-waste derived BLA, demonstrating its effectiveness as a partial replacement for OPC and as a silica source for alkaline activator production. The results showcased notable performance improvements, underscoring the substantial potential of using agricultural wastes in civil construction.